Rare type A lymphomatoid papulosis initially presenting as a giant ulcer: a case report and literature review - Chen, Xiangru; Zhang, Qingling; Zhao, Jingtong; An, Lin; Jia, Yuxi (Frontiers in Immunology, 2025)
BackgroundLymphomatoid papulosis (LyP) is a rare, chronic, recurrent, self-healing, indolent cutaneous lymphoproliferative disorder. Histologically, it resembles malignant lymphoma; however, its clinical manifestations are predominantly characterized by benign behaviors, including recurrent papules, nodules, and necrotic lesions.Case presentationWe report a case of a middle-aged female who initially presented with a giant ulcer on the right foot and was surgically treated at another hospital as a keratoacanthoma (KA). Over subsequent months, she developed scattered papules and nodules on the trunk and limbs. A comprehensive clinical and histopathological reassessment confirmed a diagnosis of LyP Type A. Notably, the initial ulcerative lesion represented an atypical feature of LyP rather than a conventional KA. Finally, the patient was successfully treated with methotrexate and interferon, resulting in complete resolution of the skin lesions without recurrence.ConclusionsIn summary, this case highlights that a giant ulcer exhibiting pseudoepitheliomatous hyperplasia (PEH) in histopathology may indicate LyP. Careful assessment for atypical lymphocytic infiltration and further immunohistochemical evaluation are essential for accurate diagnosis. When single clinical or histopathological findings are insufficient to provide a comprehensive understanding of the disease, thorough evaluation and dynamic monitoring are critical for diagnosing and managing complex cases.